Population genetics of an alien whitefly in China: implications for its dispersal and invasion success - Hong-Ran Li (Nature Portfolio, 2017)
Abstract Invasive genotypes may be associated with their ability to access the invasion habitat. The whitefly, Bemisia tabaci Q, has been an important agricultural pest in China since 2008. In order to identify the invasion routes and to provide insight into its invasion success in China, we analyzed the composition, distribution, and genetic diversity of mitochondrial haplotypes of B. tabaci Q. Samples were obtained from 23 provincial level administrative units in 2011, and analyses conducted based on the mtCOI. Our results revealed five haplotypes (abbreviated as Q1H1-Q1H5) were present in the Q1 subclade based on 773-bp mtCOI fragment analysis. The diversity of haplotypes indicated the B. tabaci Q populations were derived from multiple invasion sources originating from the western Mediterranean region. Among the haplotypes, Q1H1 was dominant, followed by Q1H2. The whitefly populations were generally characterized by low levels of genetic diversity based on the 773-bp mtCOI fragment. Similar results were obtained when the 657-bp fragment was analyzed using the procedure in a previous report. Potential mechanisms contributing to the dominance of the Q1H1 in China are also discussed. These results will be helpful in revealing the mechanisms that enabled the successful invasion of B. tabaci Q into the country.